Antimyeloperoxidase antibodies are a useful marker of disease activity in antineutrophil cytoplasmic antibody-associated vasculitides. Issue 10 (28th October 2008) - Terrier, B; Saadoun, D; Sène, D; Ghillani, P; Amoura, Z; Deray, G; Fautrel, B; Piette, J-C; Cacoub, P
Abstract : Objective: To evaluate the relevance of monitoring antimyeloperoxidase antibody levels in the management of antimyeloperoxidase-associated vasculitides. Methods: Thirty-eight patients with antimyeloperoxidase-associated vasculitides were included: microscopic polyangiitis (n = 18), Wegener's granulomatosis (n = 15) and Churg–Strauss syndrome (n = 5). Baseline characteristics and outcomes were recorded. Serial measurements of antimyeloperoxidase antibody levels were performed (ELISA, positive ⩾20 IU/ml). Results: All patients achieved vasculitis remission after a mean time of 2.0 months (SD 0.9), with a significant decrease in the mean antimyeloperoxidase antibody level at remission (478 vs 41 IU/ml (SD 598 vs 100); p<0.001). Twenty-eight (74%) patients became antimyeloperoxidase antibody negative. After a mean follow-up of 54 months (SD 38), 12 cases of clinical relapse occurred in 11/38 (29%) patients. Relapses were associated with an increase in antimyeloperoxidase antibody levels in 10/11 (91%) patients (34 vs 199 IU/ml (88 vs 314); p = 0.002). The reappearance of antimyeloperoxidase antibodies after achieving negative levels was significantly associated with relapse (odds ratio 117; 95% CI 9.4 to 1450; p<0.001). Antimyeloperoxidase antibodies showed a positive predictive value of 90% and a negative predictive value of 94% for relapse of vasculitis. Up to 60% of cases of relapse occurred less than 12 months after the reappearance of antimyeloperoxidase antibodies. Relapse-free survival was significantly worse for patients who exhibited a reappearance of antimyeloperoxidase antibodies than in those with persistent negative antimyeloperoxidase antibodies (p<0.001). The antimyeloperoxidase antibodies serum level was strongly correlated with the Birmingham vasculitis activity score and the disease extent index (r = +0.49; p = 0.002). Conclusion: Through monitoring, antimyeloperoxidase antibodies are a useful marker of disease activity and a good predictor of relapse in antimyeloperoxidase-associated vasculitides.